The Development of Evidence-Based Classification of Vision Impairment in Judo: A Delphi Study - Krabben, Kai J.; Ravensbergen, Rianne H.J.C.; Nakamoto, Hiroki; Mann, David L. (Frontiers in Psychology, 2019)
Objective: Most para-sports group athletes into ‘classes’ to compete against others with similar activity limitations. Judokas with vision impairment (VI) instead all compete in the same class irrespective of their level of impairment. There is considerable controversy whether this approach represents a legitimate way to structure judo competition. The aim of this study was to establish expert opinion on the requirements for an evidence-based classification system for VI judo. Method: A panel of eighteen athletes, coaches and administrators participated in a three-round Delphi review process. Expert opinions were canvased for a large range of issues related to classification in judo. Between rounds, results were summarised and further questions were asked on topics where consensus was not reached across experts. Results: The panel expressed that: (i) blind and partially sighted athletes should not compete against each other in the same class; (ii) additional measures of visual function might be needed to accurately evaluate an athlete’s impairment; (iii) the minimum impairment criteria should represent a more severe level of impairment to ensure that all those included possess a level of vision impairment that indeed decreases performance in judo; and (iv) legitimate competition could be undermined by some athletes intentionally underperforming on classification tests. The panel identified six additional measures of visual function which are not currently measured but are likely to impact judo performance, and six aspects of judo performance which are most likely impacted by vision impairment. Conclusion: Experts in the field of VI judo expressed a need to change the manner in which VI judokas are classified. This study outlines a model for establishing the impairment-performance relationship and guide the development of evidence-based classification for VI judo.